Structural characterization of silver nanoparticles produced by biogenic synthesis using SAXS - Ribeiro Junior, Ari; Yokaichiya, Fabiano; Monerjan, Eneli; Lemke, Karina; Guilger-Casagrande, Mariana [UNESP]; Lima, Renata; Fraceto, Leonardo [UNESP]; Franco, Margareth K.K.D.; Kellermann, Guinther (Elsevier, 2024)
Nanotechnology applied to the agricultural sector has highlighted in recent decades, making important contributions, including systems for pest control as biogenic nanoparticles. These nanoparticles are used to control phytopathogens, demonstrating the need to understand its composition, mechanisms of action and toxicity. Their capping of biomolecules, derived from the organism used in the synthesis, contributes to their stability and biological activity. Ag nanoparticles were produced by the fungus Trichoderma harzianum in aqueous solutions containing silver nitrate as a precursor for the silver nanoparticles. Some of the samples were exposed to the phytopathogenic fungus Sclerotinia sclerotiorum responsible for the white mold. After preparation, a fraction of the samples was submitted to physico-chemical processes to remove organic cap layer on nanoparticles surface formed during the preparation process. In this study we determined the effect of the phytopathogenic fungus and cap removal process in the average radius, radius dispersion, number density of the nanoparticles using small angle X-ray scattering (SAXS), where we considered their almost spherical shape in aqueous solution obtained by the biogenic route. The SAXS data analyses suggest that the presence of the pathogenic fungus results in a diminution of number and total volume of Ag NPs without significant effects on average radius and radius dispersion. Our results also indicate that the physic-chemical process to remove the organic cap surrounding the Ag NPs leads to a decrease in the fraction of the smaller nanoparticles.
Keywords: Biogenic silver nanoparticles; SAXS; Sclerotinia sclerotiorum; Trichoderma harzianum